Comparative Experiment on the Preparation of 99Mo/99mTc via Electron and Proton Irradiation of 100Mo - Desheng CHEN; Qinggang HUANG; Shiwei CAO; Zhi QIN (Journal of Isotopes)
99mTc derived from 99Mo，stands as the preeminent radiopharmaceutical employed extensively in medical diagnostics worldwide. Its current production mainly relies on some near-retirement nuclear reactors. Compared to reactors，particle accelerators have extremely low construction，operational，and maintenance costs，and their layouts are highly flexible. Given these circumstances，the production of 99Mo/99mTc by accelerator has become a research hotspot，with using electron-beam to irradiate 100Mo to produce 99Mo and proton-beam to irradiate 100Mo to produce 99mTc being the two most feasible methods. This article compares the advantages and disadvantages of two methods for preparing 99Mo/99mTc based on accelerators through experiments and Monte Carlo simulations. Direct production of 99mTc by proton accelerators，the advantage is higher yield，but other Tc isotopes，especially 99gTc，are produced alongside. In contrast，irradiating 100Mo by electrons not only can produce high-purity 99Mo with a simpler chemical separation process，but also make it suitable for preparing 99Mo-99mTc generators，which is relatively more advantageous.